Evaluation of Hospital Building Resilience to Earthquakes Using Soil Response and Finite Structure Dynamics Structure Analysis - Ibrahim, Zaky Majid; Mase, Lindung Zalbuin; Supriani, Fepy; Misliniyati, Rena; Amri, Khairul (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2025)
The city of Bengkulu is the capital of Bengkulu Province, which is the main center for government, health, and education activities. As the capital city, infrastructure development is important due to its proximity to the subduction zone. This study analyzes how the Tino Galo hospital building responds to seismic performance. The study began with a comprehensive field survey to collect geological information at the study site. Referring to various earthquake events at the study site, it is known that earthquakes triggered by subduction are the dominant type of earthquake that occurs. The seismic response of the soil was then evaluated to identify soil movement characteristics, including important parameters such as peak ground acceleration (PGA), spectral response acceleration, and amplification factor. The next step was to simulate earthquake wave propagation using three-dimensional modeling with the Finite Element Method (FEM) to assess the structural response of the building to earthquake shocks. The analysis results show that after evaluation using time history data from both earthquake waves, the building structure elements are in a safe condition. These findings imply that the current structural design can effectively withstand and distribute earthquake loads, so that no dimensional changes or additional reinforcement are required for the Hospital Building. This study recommends the continued application of a combined soil response and structural dynamics analysis method for buildings in earthquake-prone zones, as well as the need to utilise a broader range of earthquake data to improve the accuracy of seismic performance evaluations and support the development of future risk mitigation strategies.